Boolean Algebra Proofs Postulates and Theorems (Part 2)

Boolean Algebra Postulates and Theorems (Part 2):

Checkout this link for more.

Commutative Law:

x + y = y + x;
x .  y  = y . x;


Associative Law:

x + (y + z) = (x + y) + z;
x .  (y .  z) = (x  . y) .  z;


Distributive law:

x . (y + z) = x  .  y  + x  .  z;
x + (y . z) = (x + y) . (x + z);


De Morgan’s Law:

(x + y)’ = x’ .  y’;
(x .  y)’ = x’ + y’;


Absorption Law:

x + x  .  y = x;
x . (x + y) = x;


Absorption Law Proof:

x + x.y = x
L.H.S =>
= x.(1 + y)   [Distributive Law]
= x.1         [We know, x + 1 = x]
= x           [We know, x . 1 = x]
= R.H.S
Advertisements

Leave a Reply

Please log in using one of these methods to post your comment:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out /  Change )

Google photo

You are commenting using your Google account. Log Out /  Change )

Twitter picture

You are commenting using your Twitter account. Log Out /  Change )

Facebook photo

You are commenting using your Facebook account. Log Out /  Change )

Connecting to %s